Sistem Pendukung Pendeteksi Kebersihan Lingkungan Menggunakan Metode LSI - sukri, sukri; Trisnawati, Liza; Sidik, Abu Bakar (Jurnal Sains dan Teknologi (JSIT), 2024)
Technology is a tool that really helps human needs to carry out daily activities very easily, quickly, and practically. Monitoring data on the cleanliness of the Kerinci Pangkalan Environment is still being carried out one by one, namely in a conventional way that has not been systemized or computerized. The large amount of cleanliness data makes the Pelalawan Environmental Service often have difficulty detecting the cleanliness of the Pangkalan Kerinci Environment. This causes much needed computer technology using a detection system. This detection is one way to detect cleanliness. The purpose of this study is to facilitate field officers in detecting the environmental cleanliness of Pangkalan Kerinci. The data collection is in the form of literature studies, interviews and observations. Quantitative methods are used in this research process to be used in conducting testing. The Pangkalan Kerinci Environmental Cleanliness Detection Support System was built with the help of Latent Semantic Indexing (LSI) and firebase as a data repository. The Pangkalan Kerinci Environmental Cleanliness Detection Support System was tested using blackbox testing which was successful and a User Accaptance Test (UAT) was carried out with an average score of 90.8% from 20 respondents with the title "Very Good" which means that the officers from the Pangkalan Kerinci Environmental Cleaning Service are satisfied with the Kerinci Base Environment